2008
DOI: 10.1088/0264-9381/25/5/055004
|View full text |Cite
|
Sign up to set email alerts
|

Entropy calculation for a toy black hole

Abstract: In this note we carry out the counting of states for a black hole in loop quantum gravity, however assuming an equidistant area spectrum. We find that this toy-model is exactly solvable, and we show that its behavior is very similar to that of the correct model. Thus this toy-model can be used as a nice and simplifying 'laboratory' for questions about the full theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…In fact, as mentioned in Appendix B, some of the results that we have used to compute the entropy actually appear in [13].…”
Section: Comments and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, as mentioned in Appendix B, some of the results that we have used to compute the entropy actually appear in [13].…”
Section: Comments and Conclusionmentioning
confidence: 99%
“…It is important to mention that some operators similar to the one proposed here have been considered in the literature [10][11][12][13]. In these papers the authors have suggested to use area operators with eigenvalues defined in terms of the spins j i .…”
Section: The Flux-area Operatormentioning
confidence: 99%
See 2 more Smart Citations
“…In this case it is natural (although not necessary) to consider SU(2) (or U(1)) Chern-Simons theory with a level that scales with the macroscopic classical area k ∝ a H . This makes the state-counting (necessary for the computation of the entropy) a combinatorial problem which can be entirely formulated in terms of the representation theory of the classical group SU(2) (or U(1)): for practical purposes one can take k = ∞ from the starting point [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%